A Long‐Term Perspective on the Determinants of Treasury Bond Stripping Levels. Issue 4 (November 2014) - Bulter, Marck; Livingston, Miles; Zhou, Lei
<x xml:space="preserve">Abstract</x> We examine the proportion of individual Treasury bonds held as strips over the entire history of the STRIPS program. First, we document a secular decline in the Treasury bond stripping levels from 1985 to 2010, coincidental with the long‐term decline in the interest rates. This pattern suggests that investors purchase strips to avoid reinvestment risk and to lock in the high interest rates in the 1980s and 1990s. Second, higher coupon and longer maturity bonds are shown to be more heavily stripped. Third, the suspension of new issues of 30‐year bonds from 2001 through 2006 created a gap in the maturity structure of Treasury bonds and induced heavy stripping of 30‐year bonds issued post 2006. Our findings suggest that stripping is motivated by several factors, including interest rate risk management, tax concerns and market completion.